MAIN PROBLEMS OF CONTROL AND ASSESSMENT OF QUALITY OF STUDENTS 'KNOWLEDGE (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to the problems of the students' estimation at the high school which are revealed curing the consideration of the different approaches to the valuation process by the author.
Keywords: control; estimation; quality of knowledge